1987
DOI: 10.1007/bf02554940
|View full text |Cite
|
Sign up to set email alerts
|

Radiopaque markers transit and anorectal manometry in 16 patients with multiple sclerosis and urinary bladder dysfunction

Abstract: Fecal incontinence and/or constipation are frequent complaints in multiple sclerosis associated with urinary bladder dysfunction, incontinence, and/or retention. Total and segmental colonic transit were studied by determination of radiopaque markers, and anorectal function by anorectal manometry, in 16 multiple sclerosis patients clinically defined (with urinary bladder dysfunction shown by urodynamic examination). Fifteen multiple sclerosis patients had constipation and 14 had increased colonic transit time; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…These techniques include assessment of rectal mucosal blood flow (a surrogate marker of gut specific autonomic innervation) and the recto-anal inhibitory reflex (RAIR). Studies of RAIR amongst patients with SCI and MS patients have shown variations of the amplitude and time course of reflex [13][14][15]. These variations have been tentatively attributed to extrinsic nerve disruption.…”
Section: Introductionmentioning
confidence: 92%
“…These techniques include assessment of rectal mucosal blood flow (a surrogate marker of gut specific autonomic innervation) and the recto-anal inhibitory reflex (RAIR). Studies of RAIR amongst patients with SCI and MS patients have shown variations of the amplitude and time course of reflex [13][14][15]. These variations have been tentatively attributed to extrinsic nerve disruption.…”
Section: Introductionmentioning
confidence: 92%
“…Constipation may be associated with either prolonged colonic transit time,8 or with pelvic floor dysfunction 819 20 Altered colonic compliance in patients with advanced multiple sclerosis21 may be a factor.…”
Section: Discussionmentioning
confidence: 99%
“…As pelvic floor incoordination has often been reported in multiple sclerosis,8 biofeedback may have a role for those patients with impaired evacuation. Moreover, the finding of an increased threshold of rectal sensation in incontinent patients with multiple sclerosis3 9 provides a focus for improving sensory awareness.…”
mentioning
confidence: 99%
“…Weber et al (1987) in a study of 16 MS patients reported that transit times of radiopaque markers led to an objective confirmation of constipation in 13 of the 15 patients. Interruption of sympathetic innervations from the dorsolumbar spinal cord via the superior mesenteric ganglion and vagal parasympathetic innervations to the right colon together with sympathetic innervations from the dorsolumbar spinal cord via the inferior mesenteric ganglion and parasympathetic innervations from the sacral spinal cord via the erigentes nerves to the left colon were proposed to explain the decreased transit observed in MS patients (Weber et al 1987). Wald (1986) reported that prolonged transit time throughout the entire colon among MS patients responded poorly to treatment compared to those characterized by slow transit restricted to the left colon or delay only through the anorectal structures.…”
Section: Constipationmentioning
confidence: 97%
“…Pathologic conditions include phasic colonic motor activity; diminished gastrocolonic response following a meal; the high amplitude, prolonged duration, propagated contractions are decreased; and the velocity of propagation is slower, waves have a greater tendency to abort prematurely, and their amplitude is also decreased (Rao, 2007). Weber et al (1987) in a study of 16 MS patients reported that transit times of radiopaque markers led to an objective confirmation of constipation in 13 of the 15 patients. Interruption of sympathetic innervations from the dorsolumbar spinal cord via the superior mesenteric ganglion and vagal parasympathetic innervations to the right colon together with sympathetic innervations from the dorsolumbar spinal cord via the inferior mesenteric ganglion and parasympathetic innervations from the sacral spinal cord via the erigentes nerves to the left colon were proposed to explain the decreased transit observed in MS patients (Weber et al 1987).…”
Section: Constipationmentioning
confidence: 99%